Co‐Delivery of G‐CSF and EPO Released From Fibrin Gel for Therapeutic Neovascularization in Rat Hindlimb Ischemia Model. (11th July 2013) - Chen, Feng; Liu, Qi; Zhang, Zhen D.; Zhu, Xian H.
Abstract: Objective: G‐CSF and EPO have shown a notable capability in neovascularization. However, their use is limited because of untoward leucocytosis, erythrogenesis, and short half‐life in the plasma. Herein, we examined whether G‐CSF and EPO released from fibrin gel injected into ischemic tissues would synergistically promote neovascularization with limited systematic effects in a rat hindlimb ischemic model. Methods and Results: In vivo study, group Gel received an intramuscular injection of fibrin gel; group Gel+G‐CSF received fibrin gel containing human G‐CSF; group Gel+EPO received fibrin gel containing human EPO; group Gel+G‐CSF&EPO received fibrin gel containing G‐CSF and EPO; group G‐CSF&EPO received G‐CSF and EPO. Through promoting the expression of SDF‐1, local high concentration of EPO could traffic CXCR4+ cells mobilized by G‐CSF to enhance neovascularization in ischemic muscle. The treatment with Gel+G‐CSF&EPO was superior to the other treatments on blood flow reperfusion, capillary density, and α smooth muscle actin‐positive vessel density. And this treatment induced a modest WBC count increase in peripheral blood. Conclusions: G‐CSF and EPO released from fibrin gel had a combined effect on postischemia neovascularization. This treatment may be a novel therapeutic modality for ischemic peripheral artery disease.